Male infants with hypospadias and/or cryptorchidism show a lower 2D/4D digit ratio than normal boys. Issue 7 (16th February 2015) - Abbo, O; Ferdynus, C; Kalfa, N; Huiart, L; Sauvat, F; Harper, L H
Abstract : Background: In humans the ratio of the index finger to the ring finger is sexually dimorphic, with the mean ratio being larger in women than in men. It has been suggested that this difference is related to prenatal androgen exposure. This has been further demonstrated in children with congenital adrenal hyperplasia. Normal development of the male external genitalia is linked to androgen-mediated events during gestation. We therefore wanted to determine if the 2D:4D digit ratio was normal in boys with cryptorchidism or hypospadias. Methods: We prospectively enrolled all prepubertal patients seen in the outpatient clinic for cryptorchidism or hypospadias between September and December 2012. We then compared their 2D:4D digit ratio with two control groups made up of normal boys and normal girls. Interobserver and intraobserver variability was evaluated. Results: We included 57 boys with hypospadias and/or cryptorchidism, 79 boys without genital abnormalities and 25 girls without genital abnormalities. The mean 2D:4D ratio for both hands was significantly different between the three groups, with the digit ratio for boys with genital anomalies being lower than for normal boys and normal girls (p<0.0001). Conclusions: It appears that boys with genital abnormalities (cryptorchidism and/or hypospadias) have a lower 2D:4D digit ratio than boys without genital anomalies.